2018
DOI: 10.1111/bjd.15769
|View full text |Cite
|
Sign up to set email alerts
|

Severe hidradenitis suppurativa responding to treatment with secukinumab: a case report

Abstract: An inappropriate immunological response to an unknown antigen has been suggested to play a role in the pathogenesis of hidradenitis suppurativa (HS). Studies have identified elevated levels of several proinflammatory cytokines, including interleukin (IL)-17A and tumour necrosis factor-α, nominating these as possible therapeutic targets. Secukinumab is an IL-17A monoclonal antibody, which binds to IL-17A and inhibits the cytokine interaction with the IL-17 receptors, inhibiting the inflammatory cascade. Here we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 20 publications
2
57
0
1
Order By: Relevance
“…Dermatologic-specific questionnaires, such as DLQI [13], do include more of these dimensions, but still, many of the items identified in this study are not represented. As a result, it is possible that an HS patient can experience a meaningful improvement in his or her perceived QOL following a given intervention, without this improvement being reflected in, e.g., an improved DLQI score [21]. A HS-specific instrument, in contrast, has the potential of being more sensitive to change.…”
Section: Discussionmentioning
confidence: 99%
“…Dermatologic-specific questionnaires, such as DLQI [13], do include more of these dimensions, but still, many of the items identified in this study are not represented. As a result, it is possible that an HS patient can experience a meaningful improvement in his or her perceived QOL following a given intervention, without this improvement being reflected in, e.g., an improved DLQI score [21]. A HS-specific instrument, in contrast, has the potential of being more sensitive to change.…”
Section: Discussionmentioning
confidence: 99%
“…Of the IL‐17 neutralizing monoclonal antibodies seculinumab, ixekuzumab and brodalumab, only seculinumab has been approved for the treatment of psoriasis and psoriatic arthritis . It has recently been reported that HS exhibits a clinical response to seculinumab . Current therapeutic efforts focus on attenuating IL‐17 signalling in HS …”
Section: Therapeutic Agents Affect the T Helper 17 Cell/regulatory T‐mentioning
confidence: 99%
“…[217][218][219] It has recently been reported that HS exhibits a clinical response to seculinumab. 220,221 Current therapeutic efforts focus on attenuating IL-17 signalling in HS. 133,222,223…”
Section: Biologicsmentioning
confidence: 99%
“…For example, biologics potentially provide rich pickings for repurposing as the field of proteomics uncovers new disease processes. The recent report of secukinumab used for the first time in severe hidradenitis suppurativa based on the role of interleukin‐17A in the disease is such an example . Similarly, the first report of liraglutide, a glucagon‐like peptide‐1 agonist with anti‐inflammatory and weight reducing properties, used in severe hidradenitis is another .…”
mentioning
confidence: 99%